Ageism in the time of COVID-19. (February 2021) - Swift, Hannah J.; Chasteen, Alison L.
In this article, we outline how the response to the coronavirus (COVID-19) pandemic has the potential to fundamentally change how we think and feel about our own age, and how we think and feel about other age groups. Specifically, we outline how discourse surrounding the pandemic has strengthened the homogeneous view of older adults as vulnerable, has socially stigmatized being an older adult, and has exacerbated hostile and benevolent expressions of ageism. We explore the impact of these changing dynamics on intergenerational cohesion and relations, and propose that understanding theories of ageism will be essential for how we handle future pandemics in order to reduce the potential negative impact of crises on individuals as well as on communities and societies.